Hubungan antara Loneliness dengan Problematic Internet Use pada Remaja Akhir Pengguna Sosial Media di Fakultas Psikologi Universitas Medan Area - Tasya Namira; Shirley Melita Sembiring (Tabularasa: Jurnal Ilmiah Magister Psikologi, 2023)
This study aims to determine how big the correlation between Loneliness and Problematic Internet Use in late adolescent using social media at the Faculty of Psychology University of Medan Area. The hypothesis in this study is that there is a positive relationship between Loneliness and Problematic Internet Use in late adolescent. The subjects of this study found 62 people who were taken using Purposive Sampling. The data collection method in this study is a scale consisting of the Loneliness scale and the Problematic Internet Use scale. The data analysis method used in this research is Pearson's product moment correlation technique. From the results of the analysis, it is known that the hypothesis is accepted with a value of ( ) = 0.705 with a significance of p = 0.000 0.05. This means that there is a positive relationship between Loneliness and Problematic Internet Use, with the assumption that the higher Loneliness, the higher the Problematic Internet Use in late adolescents at the Faculty of Psychology University of Medan Area and vice versa, the lower Loneliness the lower Problematic Internet Use in late adolescents at the Faculty of Psychology University of Medan Area. Loneliness contributes 49.7% to Problematic Internet Use.